Penanaman Nilai-Nilai Karakter Anak Usia Dini Melalui Pembiasaan Dan Keteladanan - Evi Nur Khofifah; Siti Mufarochah (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Character values ​​are positive traits, character and personality that are useful for others.The purpose of this study was to describe the activities of inculcating character values ​​through habituation and example of group A at RA Ihyaul Ulum Kedamean Gresik. The research method used in this research is descriptive qualitative research with a case study approach. Data collection techniques used are semi-structured interviews, participant observation, and documentation. Based on the results of research that has been carried out by researchers on the children of group A RA Ihyaul Ulum Kedamean Gresik, that the character values ​​that are observed and are often raised in this educational unit through habituation and example there are 7 characters, namely religious, responsibility, tolerance, discipline, friendly/communicative, peace-loving, and socially caring.